GENUS XANTHOPIMPLA SAUSSURE, 1892 (ICHNEUMONIDAE: PIMPLINAE) FROM POTHWAR REGION (PUNJAB) OF PAKISTAN - S. Ahmed; I. Bodlah 1 M. F. Nasir; M. S. Nadeem (Journal of Animal and Plant Sciences, 2020)
Members of Genus Xanthopimpla Saussure, 1892 (Hymenoptera: Ichneumonidae: Pimplinae) are reported as important bio-control agents of different insect pests of various crops. Four species were recorded from Pothwar region with Xanthopimpla reicherti Krieger, 1914 as new record for Pakistan. New distributional records for Xanthopimpla punctata Fabricius, 1781, Xanthopimpla stremmator Thunberg 1822, and Xanthopimpla flavolineata Cameron, 1907 in Pothwar have been added. Comparison of recorded species with closely related species, distribution ranges, and remarks on their host are given. An identification key of recorded species, as well as brief description of each species has been provided, and supplemented with illustrations using microphotography from the external morphological details. Arc GIS software was used for spatial distribution of identified species. Results of these studies including illustrations may be helpful for field workers for identification and researchers to formulate IPM strategies against various insect pests of crops in different districts of Pothwar region of Pakistan.
Keywords: Ichneumonidae; Pimplinae; Xanthopimpla; Pothwar; New country record